A generalized Montgomery phase formula for rotating self-deforming bodies - Cabrera, Alejandro (2007)
We study the motion of self-deforming bodies with non-zero angular momentum when the changing shape is known as a function of time. The conserved angular momentum with respect to the center of mass, when seen from a rotating frame, describes a curve on a sphere as happens for the rigid body motion, though obeying a more complicated non-autonomous equation. We observe that if, after time , this curve is simple and closed, the deforming body’s orientation in space is fully characterized by an angle or phase θM. We also give a reconstruction formula for this angle which generalizes R. Montgomery’s well known formula for the rigid body phase. Finally, we apply these techniques to obtain analytical results on the motion of deforming bodies in some concrete examples.